Numerical methods and their application in dynamics of structures - Vasiljević, Rade R. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The aim of this paper is to analyse the numerical methods for solving differential equations of dynamic equilibrium in technical problems. Methods: The paper gives an overview of the following numerical methods: the method of central difference, the method of linear acceleration, the Newmark method, and the Wilson θ method. Results: Various problems in applying numerical methods in dynamics of structures have been solved. Conclusion: It has been shown that the application of numerical methods has a fundamental importance in dynamics of structures.